Perencanaan Business Intelligence untuk Strategi Pengembangan Produk Unggulan Menggunakan Algoritma Support Vector Machine - Oding Herdiana (Jurnal Informatika, 2023)
The government continues to encourage the government to accelerate Small and Medium Enterprises (SMEs) flagship products to enter the digital market, because the current digitalization of SMEs cannot be ignored, SMEs must be able to change their business to the digital realm. The strategy for developing superior SME products needs to be well planned, because a good and measurable strategy is very important for policy making. Development uses an approach that emphasizes that the driving force of development is commodities that are considered to be superior, both at the domestic, national and international levels. Superior products that have quality and are needed by customers require the right selection process, so we need a method to produce this information. Business Intelligence (BI) is a global term for all processes, techniques, and tools that support business decision making based on information technology. The strategy for developing superior products for SME products uses the criteria of production data, income, and SME respondent data in determining the priority list. A good product assessment based on priority can be done by BI using the classification method with the Support Vector Machine (SVM) algorithm. The research method carried out for planning the development of superior products for MSMEs in Tasikmalaya City is a research development research. To complete the classification of the right superior product development strategy, then Support Vector Machine algorithm can be used with test results using the Confusion Matrix with an average accuracy of 97%.